DESIGN OF A HIERARCHICAL GROUP TO REALIZE A SCALABLE GROUP - NISHIMURA, YASUTAKA; HAYASHIBARA, NAOHIRO; ENOKIDO, TOMOYA; TAKIZAWA, MAKOTO (Journal of Mobile Multimedia, 2005)
According to the advance of computer and network technologies, information systems are getting scalable. Especially, peer-to-peer (P2P) overlay networks and Grid computing system are now taking a central position in information systems. In these systems, a large number of peer processes are cooperating. In group communication, each peer process sends a message to multiple processes while receiving messages from multiple processes. Here, messages transmitted are required to be causally/totally delivered to every common destination of the messages. The computation and communication complexity is O(n) to O(n2) for the number n of peer processes. In order to reduce the overheads, a group is divided into smaller subgroups where processes exchange messages with other subgroups only through gateway processes while processes directly exchange messages in each subgroup. In this paper, we discuss a hierarchical group protocol aiming at reducing communication and computation overheads for supporting a scalable group of cooperating peer processes. In traditional hierarchical group protocols, each subgroup communicates with another subgroup through a single gateway communication link. A gateway communication link among subgroups implies performance bottleneck and a single point of failure. In order to increase the throughput and reliability of inter-subgroup communication, messages are in parallel transmitted in a network striping way through multiple channels between multiple processes in the subgroups. We discuss a striping multi-channel inter-subgroup communication protocol (SMIP). We evaluate SMIP in terms of stability of bandwidth and message loss ratio and show how SMIP can support more stable bandwidth and message loss ratio.